PERAN OJK DALAM PERLINDUNGAN KONSUMEN PERBANKAN SYARIAH PERSPEKTIF EKONOMI ISLAM - Nola, Indra; Hakim, Miftahur Rahman (Robust: Research of Business and Economics Studies, 2023)
The Financial Services Authority is an independent institution and free from interference from other parties that have functions, duties, authorities as regulation, supervision, and protection. The consumer protection function of the Financial Services Authority is contained in the Financial Services Authority Regulation Number 1 / POJK.07 / 2013 concerning Consumer Protection in the Financial Services Sector, Financial Services Authority Regulation Number 1 / POJK.07 / 2014 concerning Alternative Dispute Resolution Institutions, as well as Consumer Service and Complaint Resolution to Financial Service Institutions contained in the Financial Services Authority Circular Letter Number 2 / SEOJK.07 / 2014. The purpose of this study is to describe the form of implementation of consumer protection based on an Islamic economic perspective carried out by the Financial Services Authority of the Special Region of Yogyakarta (DIY) in handling consumer complaints in the Islamic banking sector. Research methods are qualitative methods through interviews, observation, and documentation. From the research, it is known that the Implementation of the Financial Services Authority in Consumer Protection in the Sharia Banking Sector has been well implemented in accordance with applicable laws and regulations and the application of principles in accordance with consumer protection in an Islamic economic perspective according to Alimin's theory.